2020
DOI: 10.1101/2020.06.20.20136325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 lockdown: if, when and how

Abstract: Background: With the lack of an effective SARS-CoV-2 vaccine, mathematical modeling has stepped up in the COVID-19 management to guide non-pharmaceutical intervention (NPI) policies. Complete lockdown has been characterized as the most powerful strategy for the epidemic; anyhow, it is associated with undeniable negative consequences. Not aware that global panic could make countries adopt premature and lengthy lockdowns, previous studies only warned about the inefficacy of late quarantine sets. Therefore, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…A study has shown that strict mitigation measures, if implemented in a timely manner, greatly outperform lengthy quarantines and lockdowns. 43 Social distancing is regarded as the most effective measure for mitigation of the disease 44 ; additionally, early lockdown reduces the effects of the disease. 45 The experience of China suggested that social distancing is a deliberate effort to slow down the spread of infectious or contagious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that strict mitigation measures, if implemented in a timely manner, greatly outperform lengthy quarantines and lockdowns. 43 Social distancing is regarded as the most effective measure for mitigation of the disease 44 ; additionally, early lockdown reduces the effects of the disease. 45 The experience of China suggested that social distancing is a deliberate effort to slow down the spread of infectious or contagious diseases.…”
Section: Discussionmentioning
confidence: 99%